Organizational Culture and Radical Technological Change: The Railway Locomotive Industry During the Twentieth Century - Churella, Albert (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1998)
AbstractBeginning in the 1930s, North American railroads began replacing their steam locomotives with diesels at an ever-accelerating rate. Established steam locomotive producers, most notably the American Locomotive Company and the Baldwin Locomotive Works, proved incapable of dealing with this radical technological discontinuity. As successful steam locomotive manufacturers, these firms developed a corporate managerial culture that was not only linked closely to steam locomotive technology; it also embodied the fundamentals of small-batch custom manufacturing. More successful competitors, such as Electro-Motive (later a division of General Motors), developed a corporate culture amenable to both diesel locomotive technology and the standardized near-mass-production techniques that made diesel production efficient and profitable. Electro-Motive executives understood that railroad customers increasingly valued performance characteristics (flexibility, lower operating costs) best fulfilled by diesels, while steam locomotive producers continued to concentrate on the outdated characteristics (horsepower, low initial cost) of steam locomotive technology.